Fresh Produce Safety and Quality: Chlorine Dioxide’s Role - Malka, Siva Kumar; Park, Me-Hea (Frontiers in Plant Science, 2022)
Maintaining microbial safety and quality of fresh fruits and vegetables are a global concern. Harmful microbes can contaminate fresh produce at any stage from farm to fork. Microbial contamination can affect the quality and shelf-life of fresh produce, and the consumption of contaminated food can cause foodborne illnesses. Additionally, there has been an increased emphasis on the freshness and appearance of fresh produce by modern consumers. Hence, disinfection methods that not only reduce microbial load but also preserve the quality of fresh produce are required. Chlorine dioxide (ClO2) has emerged as a better alternative to chlorine-based disinfectants. In this review, we discuss the efficacy of gaseous and aqueous ClO2 in inhibiting microbial growth immediately after treatment (short-term effect) versus regulating microbial growth during storage of fresh produce (long-term effect). We further elaborate upon the effects of ClO2 application on retaining or enhancing the quality of fresh produce and discuss the current understanding of the mode of action of ClO2 against microbes affecting fresh produce.